ON THE OENOCYTES OF CORCYRA CEPHALONICA (STAINTON) DURING THE POST-EMBRYONIC DEVELOPMENT (LEPIDOPTERA : PYRALIDAE) - SAINI, D. K.; ROSE, H. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
Two generations of oenocytes i. e. larval and imaginal have been noticed in C cephalonica (Stainton) The number and size of the larval oenocytes increase as the larva grows older. The larval oenocytes disintegrate during the pupal period and new imaginal oenocytes develop from the seg mental groups of cells in the epidermis of abdomen in the vicinity of spiracular tracheae.